Modifikasi Perencanaan Gedung Parkir Klandasan menggunakan Metode Flat Slabs dengan Drop Panel dan Shear Wall - Praditya, Iqbal Noverio; Muntaha, Mohammad; Basyaruddin, Basyaruddin (SPECTA Journal of Technology, 2023)
The Klandasan Parking Building (GPK) is an 8-story parking built in Balikpapan that serves as vehicle parking and uses a conventional structure system (columns, beams, plates) where the highest beam is about 800 mm. To maximize the clearance of each story, an alternative structure system is planned by removing beams called flat slabs. The new plan is conducted by modifying the structure into a dual system which consists of an Intermediate Moment Resisting Frame, a flat plate with drop panels used to withstand gravitational loads on buildings and a Structural Wall System (SWS) installed to resist lateral loads such as earthquake and wind. Structure’s plan refers to SNI 03-2847-2013 and SNI 03-1726-2012 which are Indonesia’s concrete and earthquake codes respectively. In addition, PPURG 1987 is also used to determine loads for the building. The analysis result shows that the building could be changed from 8 to 9 stories using the same total height of 8 stories. The depth of plates and drop panels which are supported by interior and exterior columns are 250 mm and 100 mm respectively. Turning to the shear wall, a thickness of 350 mm can be used to resist lateral loads.